TINDAK TUTUR DIREKTIF BAHASA INGGRIS DALAM TRANSKRIP DIALOG FILM NANNY MCPHEE (KajianPragmatik) - , MAYASITA NURUL AINI; , Prof. Dr. Soepomo Poedjosoedharmo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research paper is aimed at describing the aspects that related to the realization of directive speech act in English, both type of speech act, the meaning, and the factors influencing the choice of form of directives speech act. This research is descriptive qualitative research. The research is conducted based on three steps to answer the question research. First, collecting data from transcript dialogue using observation method also recording techniques and notetaking technique. Second, analyzing and interpreting data based on related theory using contextual method and also distributional method as additional method. Third, reporting the paper using informal method. The results of the study showed three answers. First, that type of directive English speech act done in four types. They are direct, indirect, literal, and nonliteral. In addition, they are three types based on combination between direct/indirect and literal/nonliteral, such as direct literal, direct nonliteral, indirect nonliteral. Second, the meaning of the directive speech act can be command, request, suggestion, invitation, excuse, prohibition, permission, satirize, warning, asking, apology, and entrust. Third, the choosing of the type of speech act effected by some factors. They are participants background (such age, characters, solidarity, and social-economy background/social statues), emotion, speech act situation, aim of speech act,and norm.